2011
DOI: 10.1007/s00425-011-1493-x
|View full text |Cite
|
Sign up to set email alerts
|

Light affects ascorbate content and ascorbate-related gene expression in tomato leaves more than in fruits

Abstract: Little is known about the light regulation of vitamin C synthesis in fruits. In contrast, previous studies in leaves revealed that VTC2 (coding for GDP-L: -galactose phosphorylase) was one of the key genes up-regulated by light in leaves. Our objective was to determine how the expression of ascorbate (AsA) synthesis genes in tomato (Solanum lycopersicum) was modified according to light irradiance in both leaves and fruits. Seven days of shading strongly decreased total ascorbate (reduced and oxidized form) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
68
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 39 publications
9
68
0
1
Order By: Relevance
“…1). In accordance to our results, Massot et al (2012) reported almost two-fold difference in concentration of tAsA in leaves than in fruits of tomato. Our results revealed that the most active fruit tissue is the pericarp, where transcripts were, in most cases, almost twofold higher compared to the pulp.…”
Section: Asa Metabolism In Flower and Fruit Compartmentssupporting
confidence: 92%
See 1 more Smart Citation
“…1). In accordance to our results, Massot et al (2012) reported almost two-fold difference in concentration of tAsA in leaves than in fruits of tomato. Our results revealed that the most active fruit tissue is the pericarp, where transcripts were, in most cases, almost twofold higher compared to the pulp.…”
Section: Asa Metabolism In Flower and Fruit Compartmentssupporting
confidence: 92%
“…In contrast, transcripts of most of the genes exhibited lower accumulation in fruits than in tissues with high photosynthetic potential as well as in roots. These results can be attributed into two factors; the differences in light effect in fruit and in organs with high photosynthetic potential (Massot et al 2012) and the different respira-tion rate between mature fruits and fast growing organs as flowers and root tips. Indeed, both factors are reported to have an effect on AsA metabolism (Bartoli et al 2006).…”
Section: Asa Metabolism In Flower and Fruit Compartmentsmentioning
confidence: 99%
“…Three tomato genes were targeted: the SlGMP2 gene (SGN-U568548) encoding the GDP-d-mannose pyrophosphorylase (GMP), the SlGME1 (SGN-U581327) encoding the GDP-d-mannose epimerase and the SlGGP2 gene (SGN-U579800) encoding the GDP-l-galactose phosphorylase. Selection of the genes was done based on their expression patterns in the fruit, regulation by light (Massot et al 2012) and differential expression in a AsAdeficient GME-silenced tomato transgenic line ).…”
mentioning
confidence: 99%
“…Same explanation may hold true for the GME1-5944 line, though the mild ascorbate phenotype observed in this line may also result from the creation of a weak allele by the missense mutation. More unexpected is that, despite the expression of two genes encoding GDP-l-galactose phosphorylase in tomato (Massot et al 2012), the two independent Slggp2 truncation and splice junction mutant lines have only ∼5% residual ascorbate content in the leaves (Figure 3). This result indicates that the two GGP genes found in tomato are not functionally redundant and are unable to complement each other in the conditions studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation